OPTIMIZATION OF HAULING AND DIGGING-LOADING COSTS USING LINEAR PROGRAMMING AND BUNCHING EFFECT ANALYSIS IN PT XYZ'S OPERATIONAL AREA - Pramuditho Apriliano, Gemma
In carrying out fleet matching, the match factor or equipment compatibility is one of the main parameters in determining the number of tools and production targets as well as parameters to see whether the equipment is working optimally. However, in a planning and theoretical calculation, each tool is considered to have the same efficiency whereas in its implementation, each tool has its own efficiency due to the influence of controlled and uncontrolled factors. The difference between the theoretical calculations during planning and the actual conditions in the field causes the bunching effect to occur so that the equipment does not work optimally. Bunching effect is the tendency for conveyances to move together due to differences in the efficiency of each tool, caused by controlled and uncontrolled factors. As a result of the bunching effect, the mining process carried out at PT XYZ is still ineffective and inefficient, particularly the loading and transportation of material from the loading point to the dumping point. Therefore, in this study, optimization will be carried out so that the mining process becomes more effective and efficient. Optimization is the process of making something output more effective and efficient. If optimization is a process, the result of optimization is a mining process that has become more effective and efficient by minimizing costs and maximizing production results. The method used in the optimization in this study is a linear program. The observation location limitation is on the transportation route from loading point T03 to dumping point TD11 and from loading point T03 to dumping point TD11. The types of dump trucks observed were CAT 777D with a real capacity of 80 tons and CAT 785C with a theoretical capacity of 120 tons. While the shovel observed was the Hitachi EX-1900 with a 12 m3 bucket capacity. In this study, two alternative scenarios were used, with a combination of different types of dump trucks, in order to produce the minimum freight and excavation-loading costs with the most ideal match factor value and the lowest bunching time value. In scenario 1, CAT 785C dump truck and Hitachi EX-1900 shovel are used. In scenario 2, a CAT 777D dump truck and a Hitachi EX-1900 shovel were used. The analysis shows that scenario 1 provides the most minimum transportation and excavation-loading costs with a more maximum production amount per day. Scenario 1 results in a transportation and excavation-loading cost of $ 0,649/ton with total production of 31.882,48 ton/day and bunching time value on route 1 of 0.24 minute/cycle and on route 2 of 0.25 minute/cycle.